Advances in the mechanism of small extracellular vesicles promoting the development of hepatocellular carcinoma through multi-network fusion - Yuan, Xiaoying; Huang, Defa; Peng, Liang; Lin, Yilong; Wang, Lijuan; Yan, Jiawei; Qiu, Youming; Song, Chenggui; Wang, Qi (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) is a highly malignant epithelial tumor characterized by global high incidence and poor clinical prognosis. Radical surgical resection, as the standard treatment for early-stage HCC patients, has been extensively validated for its therapeutic efficacy. However, epidemiological studies indicate that most patients are already in advanced stages at initial diagnosis, losing eligibility for radical treatment. Notably, HCC pathogenesis exhibits marked etiological heterogeneity, posing significant challenges for clinical management. Although significant breakthroughs have been made in understanding HCC drivers at pathophysiological levels, translational applications of these findings remain hindered by multiple barriers. Currently, elucidating the molecular mechanisms of HCC pathogenesis and identifying effective therapeutic targets constitute major research priorities in this field.Small extracellular vesicles (sEVs) are phospholipid bilayer vesicles (30-150 nm in diameter) carrying functional proteomes and nucleic acids (e.g., miRNAs, lncRNAs) with substantial biological activity. Studies demonstrate that sEVs contribute to malignant phenotype acquisition by modulating key signaling pathways such as PI3K/AKT and Wnt/β-catenin. These molecular cascades ultimately confer hallmark pathological features including aberrant proliferation, apoptosis resistance, and immune evasion to tumor cells. Within multi-network regulatory systems, sEVs serve as crucial intercellular messengers mediating tumor cell interactions with other tumor microenvironment (TME) components (e.g., cancer-associated fibroblasts, immune cells). Such communication facilitates TME reprogramming, pro-angiogenic phenotypic shifts, and therapy resistance development. Nevertheless, the precise molecular mechanisms of sEVs in HCC pathogenesis remain incompletely understood, warranting further exploration of their translational potential in clinical practice.